Comparison of the validity and reliability of local positioning systems against other tracking technologies in team sport: A systematic review - Pino-Ortega, J.; Oliva-Lozano, J. M.; Gantois, P.; Nakamura, F. Y.; Rico-González, M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
Given the accuracy in data collection, radar-based local positioning systems (LPS) are a promising technology to monitor training load in team sports. The objective of this study was to systematically review articles that compare the validity and reliability of LPS to other electronic performance and tracking system (EPTS) in team sports. The authors searched three electronic databases (SPORTDiscus, PubMed, and Web of Science) to identify relevant studies published by October 21, 2019. A Boolean search was performed, including sport (population), search terms related to intervention technology (intervention technology), and outcome measures of the technology (outcomes). Seven studies evaluated the validity and reliability of LPS in team sports in comparison with other EPTS, including semi-automatic video technology (VID) and Global Positioning System (GPS). Two articles compared LPS to VID, three articles compared LPS to GPS, and two articles compared LPS to both GPS and VID. LPS is considered a valid and reliable EPTS in the field of load monitoring of team sports, usually resulting in higher accuracy than VID or GPS. However, special care should be taken when analyzing load indicators at high speeds or different trajectories, since the validity and reliability depend on the EPTS itself.